A study on profitability performance between Islamic banking and conventional banking / Nurul Syazana Basar - Basar, Nurul Syazana (2011)
The research applies performance evaluation of banks in Malaysia. It means evaluation how well the company performs in profitability. The main aim is achieved through ratio analysis of Islamic bank represented by Bank Islam Malaysia Berhad while conventional bank is RHB Bank. The main data was collection from the Annual Financial Report on both of banks that cover from 2004 until 2009. Different financial ratio are evaluated such capital structure and solvency, return on investment and operating profit margin. The mathematical calculation was established for ratio analysis between two banks from 2004 until 2009. The graphical analysis and comparison are applies between two banks for measurement all of types of financial ratio analysis. The profitability ratio is used to asses the capability of company to generate earning as compared to its expanses and other relevant cost incurred during certain period of time. Leverage ratios, also known as capitalization ratios, indicate how leveraged a company is in terms of debt, and how well it can handle that debt with its assets and operating income. Thus, this study evaluates how the banks manage their debts. Overall analyses are measurement the best one between Bank Islam Malaysia Berhad and RHB Bank.